Characterization of Post-Consumer PET after Removal of the Original Surface: Influence of Raw Material - Mancini, Sandro Donnini [UNESP]; Nogueira, Alex Rodrigues [UNESP]; Saide Schwartzman, Jonas Age [UNESP]; Kagohara, Dennis Akira [UNESP] (Taylor & Francis As, 2010)
Post-consumer cooking oil and soft drink PET bottles (PEToil and PETsoft drink) were ground and washed only with water (conventional washing). The polymer was then chemically washed (10min in an aqueous solution of sodium hydroxide 5mol center dot L-1 at 90 degrees C) and rinsed. The materials before and after chemical washing were characterized by intrinsic viscosity, differential scanning calorimetry, thermogravimetry, elemental analysis, scanning electron microscopy with X-ray spectrum microanalysis, and gas chromatography coupled to mass spectrometry. The results indicated that conventionally washed PEToil is the material that most differs among the four tested ones, and that the other three are more similar to each other and to what is expected for pure PET. For example, the composition of PEToil washed only in water contained 30 volatile organic compounds, 5 nonvolatile compounds, and 7 metals, while PETsoft drink washed conventionally and chemically contained 5 volatile organic compounds and no metal or nonvolatile organic compounds.
Keywords: impurities; oil bottles; PET; soft drink bottles; washing